Design and Analysis of a Compact Superwideband Millimeter Wave Textile Antenna for Body Area Network. (18th March 2022) - Khan, Mohammad Monirujjaman; Islam, Kaisarul; Shovon, Md. Nakib Alam; Abbasi, Muhammad Inam; Bourouis, Sami; Hussein, Hany S.; Alshazly, Hammam
Abstract : The advancement of wireless technology has led to an exponential increase in the usage of smart wearable devices. Current wireless bands are getting more congested, and we are already seeing a shift towards millimeter wave bands. This paper proposes a design for a millimeter wave textile antenna for body-centric communications. The antenna has a quasi-self-complementary (QSC) structure. The radiating patch is a semicircular disc with a radius of 1.855 mm and is fed by a 5.07 mm long, 0.70 mm wide microstrip feedline. A complementary leaf-shaped slot is etched in the ground plane. The radiating disc and the ground plane are attached to a 1.5 mm thick nonconducting 100% polyester substrate. The antenna has an overall dimension of 10   mm × 7.00   mm . In free space, the antenna achieved a superwideband impedance bandwidth that covers the Ka, V, and W bands designated by IEEE. At 60 GHz, the antenna's radiation efficiency was 89.06%, with a maximum gain of 5.7 dBi. Millimeter waves are easily blocked by obstacles and have low skin penetration depth. On-body investigations were carried out by placing the antenna on a human phantom at five different distances. No significant amount of back radiation was observed. The radiation efficiency decreased to 67.48% at 2 mm away from the phantom, while the maximum gain slightly increased. The efficiency and radiation patterns improved as the distance between the antenna and the phantom gradually increased. Ten different textile substrates were also used to test the antenna. With a few exceptions, the free space and on-body simulation results were very similar to polyester. The design and simulation of the antenna were carried out using the CST microwave studio.